Paris agreement: instrument of International Law in the Fight Against Climate Warming - Dubois, Alyssia (2019)
In a context where the consequences of rising temperatures are already beginning to be felt around the world, it is urgent to adopt concrete measures to slow down and limit global warming. This is the aim of the Paris Agreement, of which 196 of the 197 member states of the UN are party. However, despite ambitious targets and means that take into account the difficulties of some countries, the expected results are uncertain.